Implementasi Pembangunan Berkelanjutan Berwawasan Lingkungan Studi Pada Kelurahan Lempake Kecamatan Samarinda Utara Kota Samarinda - Zaini, M.; Darmawanto, Agus Tri (Jurnal Ilmu Ekonomi dan Pembangunan, 2015)
This study aimed to analyze the implementation of environmental sustainable development in the Urban Village Lempake District of North Samarinda Samarinda.This research object is the environment at the Village area Lempake District of North Samarinda Samarinda. This study used a type of qualitative research. Methods of data collection is done by observation, interviews, literature and documentaries. Data analysis techniques in this study using a model of Miles and Huberman.The results of this study were (i) aspects of development (development) shows that the construction of public facilities and infrastructure such as roads, bridges, water supply lines, drainage channels or ditches that have been implemented by the government in-village Lempake good enough and progress although not evenly kesejumlah significant area; (Ii) environmental aspects (environment), environmental conditions around the Village Lempake fairly clean, but still need to be improved cleanliness, public awareness and concern for the environment became a major factor in preventing and minimizing the occurrence of the problems that exist in the environment; (Iii) social aspects (society), public awareness of the environment around the Village Lempake quite good, with the activities of the mutual assistance, but still need to be improved; (Iv) economic aspects (economy), environmental conditions in the Village Lempake enough support to economic activity surrounding communities. The opportunity to work in the surrounding environment is also quite good, it can be inferred from the extent of land that can be used. Keywords: Environment, Society, EconomyJEL Classification: O44, Q56